THE CONTENT OF NEUTROPHIL GELATINASE-ASSOCIATED LIPOCALIN IN THE BLOOD SERUM OF YOUNG PATIENTS WITH ARTERIAL HYPERTENSION - Bilovol, O.M.; Kniazkova, I.I.; Mishchenko, V.M.; Kuzminova, N.V.; Kirienko, O.M.; Abolmasov, O.M.; Abramova, L.P. (World of Medicine and Biology, 2024)
The purpose of the work was to study the content of neutrophil gelatinase associated lipocalin in blood serum and its relationship with parameters of intrarenal hemodynamics in young patients with arterial hypertension. It was established that in such patients the maximum value of neutrophil gelatinase associated lipocalin content in blood serum was characteristic of individuals with a reduced glomerular filtration speed compared to patients with preserved glomerular filtration speed and healthy individuals. The duplex scan data of the renal arteries showed that in patients with arterial hypertension of young age a decrease in the end-diastolic velocity of arterial blood flow and increasing the resistance index was recorded, more pronounced when the rate of glomerular filtration decreases, that confirms their diagnostic significance in the assessment of morpho-functional changes in the kidneys.
Keywords: neutrophil gelatinase associated lipocalin; arterial hypertension in young people; duplex scanning of the renal arteries; glomerular filtration speed